Integrated Access and Backhaul: A New Type of Wireless Backhaul in 5G - Ronkainen, Henrik; Edstam, Jonas; Ericsson, Anders; Östberg, Christer (Frontiers in Communications and Networks, 2021)
In this paper, we study the concept and the potentials of integrated access and backhaul (IAB) as one of the main innovative aspects of 5G networks. We study IAB networks from different perspectives. Particularly, we summarize the recent Rel-16 discussions on IAB, and highlight the main IAB-specific agreements on different protocol layers. Moreover, we present simulations and proof-of-concept testbed results to evaluate the performance of IAB networks in both urban and suburban areas. As show, for both suburban and urban scenarios, IAB is an attractive complement to fiber, with high flexibility and low time-to-market.